Caudal Regression Syndrome - Ranjit I. Kylat; Mohammad Bader (MDPI AG, 2020)
Caudal Regression Syndrome (CRS) or Caudal dysgenesis syndrome (CDS) is characterized by maldevelopment of the caudal half of the body with variable involvement of the gastrointestinal, genitourinary, skeletal, and nervous systems. CRS affects 1-3 newborn infants per 100,000 live births. The prevalence in infants of diabetic mothers is reported at 1 in 350 live births which includes all the variants. A related condition is sirenomelia sequence or mermaid syndrome or symmelia and is characterized by fusion of the legs and a variable combination of the other abnormalities. The Currarino triad is a related anomaly that includes anorectal atresia, coccygeal and partial sacral agenesis, and a pre-sacral lesion such as anterior meningocele, lipoma or dermoid cyst. A multidisciplinary management approach is needed that includes rehabilitative services, and patients need a staged surgical approach.